State Policy in the Field of Treatment and Utilization of Food Waste in Russia - A. P. Epishov; S. E. Zhura; N. A. Epishov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
A key problem, which requires solution in today’s situation, is treatment of food waste. Nowadays food waste is mainly buried and it does harm to the environment and people’s heals, pollutes air because of dump gases (including greenhouse gases), soil and water and causes irreversible climatic changes. It is necessary to pass over to such level of production and consumption, which could minimize and even eliminate waste formation. The authors of the article substantiate the need to take steps aimed at waste involvement in economic turn-over by its recycling, which requires the development of the effective mechanism of food waste control in the Russian Federation. The economic mechanism shall include the system of normative, legal and other documents in the field of treating food waste, a set of technological and infrastructure decisions aimed at utilization of food products with expiring BB dates, methodological recommendations on cutting food waste formed in business activity and its utilization.